Social revolution. Paper of the Social Revolution Group. . Workers' power for social revolution
Till no. 2 titled: Workers' power for social revolution. Continues: Libertarian communism. Discussion journal ... - Continued by: Solidarity for social revolution. Paper ... (ZK 40804).